Electrospinning-derived “Hairy Seaweed” and its photoelectrochemical properties - Kong, Junhua (2013)
Highly porous three-dimensional (3D) hierarchical nanostructures suspended in aqueous media were facilely prepared via electrospinning of polyacrylonitrile (PAN)/indium tin oxide (ITO) nanofibers and collection of the hybrid nanofibers by water, followed by hydrothermally growing ZnO nanorods from the nanofibers. The large inter-fiber distances facilitated the uniform growth of the ZnO nanorods throughout the whole system. The suspended PAN/ITO nanofibers process excellent light trapping capability due to their centimeter-sized dimensions and hence large light penetration path. This significantly increases the probability of multiple-reflections, leading to high absorption with almost zero transmission when the size of the sample reaches 10 mm in the direction parallel to incident light. High photocurrent was generated when the nanorods-on-nanofibers was used as a photoanode. The high photocurrent density generated by the anode can be attributed to its excellent light-trapping capability brought by the large amount of interaction sites between the ZnO nanorods and light, its large contact area with electrolyte, as well as the conduction path constructed by high-content ITO nanoparticles.